Exprimental study on hydrostatic treatment of ZK60 magnesium alloy. (8th May 2019) - Zhao, Mengjun; Qiu, Rongxian; Wu, Zhilin
Abstract: The experiment of hydrostatic treatment on ZK60 magnesium alloy was conducted at 160 °C under hydrostatic pressure of 500 MPa, then the specimens were performed by using mechanical tester, optical microscopy, SEM, XRD and EDS. The mechanical results showed that the yield strength after hydrostatic pressure was enhanced by 89.1%, compared with the yield strength after aging heat treatment. And the analyses on microstructure indicated that hydrostatic pressure led to the increase of precipitates scattered on α -Mg matrix and the decrease of Zn concentration in a-Mg matrix; besides, there was a significant positive correlation between the increase of the precipitates and the decrease of Zn concentration in a-Mg matrix, which was validated by the XRD pattern and EDS spectrum analyses. It is therefore speculated that the increase the yield strength after hydrostatic pressure is possibly determined by the increase of precipitates MgZn and MgZn2 scattered on α -Mg matrix.